Polyfluorinated alkyl substances (PFAS) in high-volume air samples collected during Polarstern expedition ANT-XXIII/1 - Annika Jahnke; Urs Berger; Ralf Ebinghaus; Christian Temme (PANGAEA, 2007)
Neutral, volatile polyfluorinated alkyl substances (PFAS) were determined in high-volume air samples collected onboard the German research vessel Polarstern during cruise ANT-XXIII/1 between Bremerhaven, Germany (53° N) and Capetown, Republic of South Africa (33° S) in fall 2005. An optimized and validated analytical protocol was used for the determination of several fluorotelomer alcohols (FTOHs) as well as N-alkylated fluorooctane sulfonamides and sulfonamidoethanols (FOSAs/FOSEs). Quantitative analyses were done by gas chromatography-mass spectrometry. This study provides the first concentration data of airborne PFAS from the Southern Hemisphere. Results indicate a strongly decreasing concentration gradient from the European continent toward less industrialized regions. The study confirms that airborne PFAS are mainly restricted to the Northern Hemisphere with a maximum concentration of 190 pg/m**3 (8:2 FTOH) in the first sample collected in the channel between the European mainland and the UK. However, south of the equator, trace amounts of several FTOHs and FOSAs with a maximum of 14 pg/m**3 (8:2 FTOH) could still be detected. Furthermore, a selection of ionic PFAS including perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) were determined in the particulate phase of high-volume air samples by liquid chromatography-mass spectrometry. Levels of ionic PFAS were almost 2 orders of magnitude lower than those of neutral PFAS, with maximum concentrations in the first sample of 2.5 pg/m**3 (PFOS) and 2.0 pg/m**3 (PFOA).
Supplement to: Jahnke, A et al. (2007): Latitudinal gradient of airborne polyfluorinated alkyl substances in the marine atmosphere between Germany and South Africa (53° N-33° S). Environmental Science and Technology, 41(9), 3055 -3061, https://doi.org/10.1021/es062389h